“MINERALS”, “PETROLEUM” AND “OPERATIONS” IN THE MINERAL AND PETROLEUM RESOURCES DEVELOPMENT ACT 28 OF 2002: A GEOLOGIST AS DEVIL’S ADVOCATE FOR A CHANGE? - PJ Badenhorst; RW Shone (Obiter, 2022)
This article examines the meaning of “minerals”, petroleum, “operations” and activities in relation to such substances to determine the ambit of the application of the Minerals and Petroleum Resources Development Act 28 of 2002, the type of rights necessary for such operations and activities and the ambit of these rights. The examination of the meaning of these concepts takes place with reference to prior definitions in statutes and also from a natural science and geology perspective. An attempt is made to show that the legal definitions do no always correspond with the geological meanings and the meanings on the ground. It is questioned whether in recent legislation why more reliance is not placed on input from geologists in the field.